Short-term mortality and morbidity of very-low birth weight infants over 9 years at Groote Schuur Hospital - Dumaresq, Helen (Department of Paediatrics and Child Health, 2025)
Background: With the advancement of neonatal care there has been a decrease in mortality rates of VLBW infants worldwide. However, this has been at the cost of increased morbidity in this vulnerable group. Currently there are little up to date data on short term morbidities for VLBW infants in low and middle-income countries. Objectives: The primary objective was to describe the neonatal mortality rate in infants 401g-1500g admitted to Groote Schuur neonatal nursery over 9 years and within weight categories. Secondary objectives were to evaluate the main neonatal short-term morbidities of these infants over time and within weight categories. Methods: This study is a secondary analysis of prospectively collected observational data. All VLBW (<1501g) infants admitted to Groote Schuur Neonatal unit from 2012-2020 were included in the study. Data were benchmarked against the Vermont Oxford Network database. Results: Of the 4644 infants included in the study the overall mortality rate was 19.8%, which remained static over the study period and was higher in comparison to the VON. There was a significantly higher mortality rate associated with decreasing birth weight. The mortality rate for outborn vs inborn infants was higher: 30.3% vs 18.4% (p value 0.046). There was a significant risk of short-term morbidity in infants <1001g vs 1001- 1500g. The survival rate without major morbidity was 65.8% overall. There was a higher survival rate without morbidities with increasing birth weight. Survival rates without morbidity were comparable to that of the VON. Conclusion: The results demonstrate that mortality rates are higher in comparison to developed countries. However, importantly, survival without morbidity is comparable. Strategies to improve mortality and morbidity in VLBW infants are multifaceted and require a collaborative and innovative approach. Important strategies include an emphasis on improved antenatal care, regionalization of care, screening facilities, neonatal specific training of staff, antenatal steroids, CPAP, surfactant replacement therapy, stringent infection control procedures, kangaroo mother care and promotion of breastfeeding.